Implicit Effects on Religious Priming on Prejudice and Prosocial Behavior - Butcher, Cody; Selvanathan, Hemapreya; Jeevanba, Sathya Baanu; Timdal, Ashley; Miner, Elizabeth (My University, 2015)
We hypothesize that priming religious concepts will result in higher rates of donation to the minority organization among nonbelievers, but lower levels of donation among believers. We predict that priming with secular concepts, compared to control concepts, will result in higher rates of donation among both believers and non-believers. Regardless of priming, we also anticipate non-believers to donate more than believers. Additionally, we will evaluate religious orientation and empathy as potential correlates.
Color poster with text, graphs, and tables.
Keywords: Racial prejudice; Religious priming; Posters